Pengaruh Struktur Modal, Profitabilitas, Dan Likuiditas Terhadap Nilai Perusahaan Dengan Leverage Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Sektor Konsumsi Yang Terdaftar Di Bursa Efek Indonesia 2021-2023) - Winda Nur Satiti; Andy Dwi Bayu Bawono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of capital structure, profitability, and liquidity on firm value with leverage as a moderating variable in consumer sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research method used is a quantitative approach with secondary data in the form of company financial reports obtained through the official IDX website. The data analysis technique uses multiple linear regression and moderated regression (Moderated Regression Analysis/MRA). The results of the study indicate that capital structure has a significant effect on firm value. However, profitability and liquidity do not have a significant effect on firm value. Furthermore, leverage is unable to moderate the relationship between capital structure, profitability, or liquidity on firm value. This finding indicates that in the context of consumer sector manufacturing companies in Indonesia, leverage does not act as an effective moderating variable, and only capital structure is proven to affect firm value during the observation period.